Association of Typhoid Fever Severity with Polymorphisms at Nucleotide Oligomerization Binding Domain 2 (NOD2) and Natural Resistance Associated Macrophage Protein 1 (NRAMP1) Genes in A Sample of Iraqi Patients: Association of Typhoid Fever Severity with NOD2 and NRAMP1 Genes - Jasim Mohammed, Bushra; Yasir Azem Hameed (Iraqi Journal of Cancer and Medical Genetics, 2023)
Background and aim: Typhoid fever is one of the major health problems facing humanity of all ages. This study was conducted to investigate the relative contribution of genetic factors to the severity of typhoid fever in a sample of the Iraqi population. Materials and Methods: Blood samples were collected from 52 patients suffering from typhoid fever that was previously diagnosed using conventional and genetic methods at Ibn Al-Baladi Hospital in Baghdad and 52 apparently healthy volunteers as a control group. DNA was extracted from peripheral blood and genotyped for NRAMP1 Intron 4 (469+14 G/C) / rs3731865 and NOD2 Exon 8 (2722 G/C) / rs2066845 single nucleotide polymorphism (SNP) using the Nested T-ARMS PCR method. Results: explained that patients with at least one copy of the NOD2 (C) allele, whether (homozygote or heterozygote) had a high risk of severity of Typhoid fever with highly significant (P≤0.01), as well as results found that there was no association between the occurrence of NRAMP1 rs3731865 Intron 4 (469+14 G/C) with severity of Typhoid fever. Conclusion: The incidence of NOD2 Exon 8 (2722 G/C) rs2066845 SNP plus the C allele could be related to the severity of Typhoid fever in this particular Iraqi population.